Snuffbox fistula – a first-line approach to haemodialysis: A review. Issue 5 (September 2020) - Idrees, Marwan; Suthananthan, Arul; Pathmarajah, Tishanthan; Sieunarine, Kishore
Purpose: To examine the feasibility of snuffbox arteriovenous fistula as a first option for haemodialysis Background: Snuffbox arteriovenous fistula is the most distal native anastomosis possible for haemodialysis access. It was described by Rassat et al. This systematic review evaluates all literature investigating the feasibility and efficiency of performing snuffbox arteriovenous fistula. Methods: PubMed, Cochrane Library and Google Scholar were systematically searched for all English articles related to snuffbox arteriovenous fistula. Included studies were appraised using relevant appraisal tools. Results: Eleven papers were included, one prospective trial and the remaining being retrospective. Two trials compared snuffbox arteriovenous fistula to the standard Cimino-Brescia wrist fistula. Factors predicting success included vessel diameter, diabetes, age <70 years, male gender, palpable radial artery, central venous system patency and surgical technique. Patency rates ranged from 61% to 87% at 1-year follow-up and decreased to 36.3%–87% on longer duration follow-up. Ipsilateral radiocephalic fistula was successfully formed in 45%–100% of snuffbox arteriovenous fistula that failed (average of 73.5%). Conclusion: This is a systematic review investigating snuffbox arteriovenous fistula's efficacy. The current literature is scarce and of poor quality; however, it does reflect that, in the well-selected patient, snuffbox arteriovenous fistula is a good and valid option for first-line haemodialysis. It provides a long segment of vessel for needling and also spares the proximal vessels for future use. Ability to effectively convert to wrist fistula in the event of snuffbox arteriovenous fistula failure provides longevity to native haemodialysis access before prosthetic adjuncts are required. This review provides recommendation for well-constructed randomised controlled trials to help delineate snuffbox arteriovenous fistula efficacy and investigate factors that affect success of these fistulas.